Disturbed Yin–Yang balance: stress increases the susceptibility to primary and recurrent infections of herpes simplex virus type 1 - Yan, Chang (Acta Pharm Sin B, 2020)
Herpes simplex virus type 1 (HSV-1), a neurotropic herpes virus, is able to establish a lifelong latent infection in the human host. Following primary replication in mucosal epithelial cells, the virus can enter sensory neurons innervating peripheral tissues via nerve termini. The viral genome is then transported to the nucleus where it can be maintained without producing infectious progeny, and thus latency is established in the cell. Yin–Yang balance is an essential concept in traditional Chinese medicine (TCM) theory. Yin represents stable and inhibitory factors, and Yang represents the active and aggressive factors. When the organism is exposed to stress, especially psychological stress caused by emotional stimulation, the Yin–Yang balance is disturbed and the virus can re-engage in productive replication, resulting in recurrent diseases. Therefore, a better understanding of the stress-induced susceptibility to HSV-1 primary infection and reactivation is needed and will provide helpful insights into the effective control and treatment of HSV-1. Here we reviewed the recent advances in the studies of HSV-1 susceptibility, latency and reactivation. We included mechanisms involved in primary infection and the regulation of latency and described how stress-induced changes increase the susceptibility to primary and recurrent infections.